PENERAPAN FRAMEWORK FLUTTER DALAM MEMBANGUN APLIKASI MARKETPLACE TRAVEL UMROH DAN HAJI BERBASIS ANDROID - Mardiah Ramadhani; Ilka Zufria (UIN Sumatera Utara Medan, 2022)
The rapid development of internet technology can be felt and is very much needed in numerous industries of company when it comes to selling their products online. Marketplace is an e-commerce service that connects merchants and customers online to handle buying and selling transactions, such as creating a marketplace application. This marketplace can assist businesses in offering their products and competing in a healthy manner, one of which is the Umrah and Hajj travel agency business. The Umrah and Hajj travel marketplace can assist travel companies in marketing their products, prospective pilgrims have many travel options and desired departure packages, and prospective pilgrims can order packages online and in real time using this application. This program also has a pleasing appearance and gives menus and options to assist the congregation in doing their worship. The umrah and hajj travel application is an android-based application built using the dart programming language, flutter framework, and MySQL database used for data storage.